IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PELAJARAN BIOLOGI KELAS X DI SMA NEGERI 1 PALEMBANG - Asri Arumsari; Yuli Andravia Falensi; Didi Jaya Santri (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2023)
The learning model used by educators is expected to have an impact on student learning outcomes. This class action research (CAR) aims to implement the problem based learning (PBL) learning model on student learning outcomes in biology class X.1 at SMA Negeri 1 Palembang so that it can improve the quality of learning through giving action to students. Classroom action research carried out by the author, namely as many as three cycles. The results of this class action research (CAR) were that in the first cycle the implementation of the problem-based learning model did not affect the learning outcomes of students because 85% of students obtained grades ≤70 and 15% of students who managed to achieve scores of ≥70. Furthermore, in cycle II there was an increase in learning outcomes in the previous cycle 56% of students scored ≤70 and 44% of students who managed to get scores ≥70. And in the third cycle, 15% of students scored ≤70. and 85% of students who managed to score ≥70. From the data of cycles I, II, and III, there was an increase in student learning outcomes, so in class action research (CAR), it was stated that the problem-based learning model could affect student learning outcomes.